Consumers' Response to Sugar Label Formats in Packaged Foods: A Multi-Methods Study in Brazil - Scapin, Tailane; Fernandes, Ana Carolina; Shahid, Maria; Pettigrew, Simone; Khandpur, Neha; Bernardo, Greyce Luci; Uggioni, Paula Lazzarin; Proença, Rossana Pacheco da Costa (Frontiers in Nutrition, 2022)
Providing information about the sugar content of packaged foods on product labels is an important strategy to lower consumers' sugar intake. This study assessed the effect of exposure to different sugar labels on consumers’ understanding of the sugar content of foods and their food choices. In the first phase, five focus groups were conducted with a convenience sample of Brazilian adults to explore their perceptions about food labelling in general and sugar labelling in particular. Based on the qualitative results, four sugar label formats were developed and subsequently tested in a five-arm study on 1,277 adults via a randomised controlled online survey. The formats were: (i) no sugar information – control, (ii) total and added sugar content displayed in the Nutrition Information Panel (NIP), (iii) a front-of-package (FoP) octagonal warning for 'high-in-sugar' products, (iv) a FoP magnifying glass warning for 'high-in-sugar' products, and (v) a 'high-in-sugar' warning text embedded on the NIP. Participants from the focus groups reported being confused about the meaning of 'sugar' and 'added sugar' on food labels and indicated that more interpretive labels, such as the FoP warnings, would help them choose products with low sugar content. In the experiment, all intervention sugar label formats improved participants' understanding of the sugar content of the tested food products, with the FoP warnings (iii and iv) showing the best results. While non-significant differences among label conditions were observed for food choices, the FoP octagonal warning prompted participants to choose high-in-sugar products less often. Given current public policy agendas aiming to reduce added sugar intake, there is a need to strengthen food labelling policies and nutrition disclosure policies that target the display of added sugar and build consumer awareness in using these tools to avoid high-in-sugar products.